Peran Pemimpin KMI dalam Meningkatkan Kompetensi Guru Dirosah Islamiyah di Pondok Modern Darussalam Gontor Kampus 2 Ponorogo - Rochman, Abdul (El-Hayah, 2022)
Abstract The objective of this research is to analyze the role of the leadership of the Kulliyatu-l-Mu'allimin al-Islamiyyah in improving the competence of teachers at Dirosah Islamiyah at Pondok Modern Darussalam Gontor Campus 2 at Madusari-Siman-Ponorogo for the academic year 2021-2022. The researcher used a qualitative descriptive method. While the data analysis techniques used are: data reduction, data display, and conclusion drawing. The data collection technique with interviews, observation and documentation.. The results of this study, it was found that: (1) The role of the KMI leadership in improving the competence of teachers at the PMD Gontor Campus 2 for the 2021-2022 academic year is as an educator, manager, administrator,supervisor, leader, and innovator. Keywords: KMI Leaders; Teacher Competence; and Islamic Teacher